2005
DOI: 10.1007/s11085-005-4394-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water-Vapor Content and Gas Flow Rate on the Oxidation Mechanism of a 10%Cr-Ferritic Steel in Ar-H2O Mixtures

Abstract: The oxidation behavior of a Ferritic 10%Cr steel in Ar-H 2 O mixtures was investigated at temperatures between 550 and 650 • C. The studies aimed at elucidating the effect of water-vapor content as well as the gas flow rate on the mechanisms of oxide-scale formation. It was found that, the oxide types and morphologies depend on time and exposure conditions. An important observation is that H 2 produced by the reaction of water vapor with the steel can play a significant role in the oxidation process. First, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…This effect is frequently observed in case of oxide scales exhibiting very high growth rates (see e.g. [20]). -As result of the reaction of the water vapor with the metal, minor amounts of H 2 are formed.…”
Section: O 4 From Incorporation Of Internal Oxidesmentioning
confidence: 60%
See 2 more Smart Citations
“…This effect is frequently observed in case of oxide scales exhibiting very high growth rates (see e.g. [20]). -As result of the reaction of the water vapor with the metal, minor amounts of H 2 are formed.…”
Section: O 4 From Incorporation Of Internal Oxidesmentioning
confidence: 60%
“…-As result of the reaction of the water vapor with the metal, minor amounts of H 2 are formed. It is easy to derive [20] that at the prevailing temperature this effect leads to a substantial decrease in the equilibrium oxygen partial pressure of the gas if the amount of hydrogen exceeds about 10 ppm. Which of these mechanisms is responsible for the FeO formation in contact with the gas cannot be derived with certainty from the present results.…”
Section: O 4 From Incorporation Of Internal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The real oxygen concentration at the magnetite/atmosphere interface is not the oxygen concentration in air or water. Zurek et al [20], who studied oxidation of 10% Cr ferritic steel in Ar-H 2 O mixture, showed that the oxide scale thickness does not depend on the H 2 O content in the gas mixture (Ar-4% H 2 O or Ar-50% H 2 O) if the oxygen activity is sufficient to allow the thin hematite layer formation. The estimated oxygen partial pressure using Henry's constant of SCW is lower than that of steam.…”
Section: Determination Of Iron Diffusion Coefficient Inmentioning
confidence: 99%
“…Many studies have shown that oxidation rates in humid environment are relatively higher than in dry environment. [2][3][4][5][6] A possible mechanism is that water vapor retards the formation of protective scale. Extensive works have been done to understand the role of water vapor in impeding the formation of protective Cr 2 O 3 scale, but the explanations remain in qualitative manner.…”
Section: Introductionmentioning
confidence: 99%